Methods of Literacy Research: The Methodology Chapters From the Handbook of Reading Research, Volume III, 1st edition - Michael L., Kamil (Routledge, 2020)
In this volume, 10 reviews of significant reading research methodologies are reprinted from the Handbook of Reading Research, Volume III. The editors have judged that these specific methodologies have had great impact on reading research since the publication of Volume II in 1991. This text is especially well-suited for use in upper-level undergraduate and graduate-level reading research methods courses.